2012
DOI: 10.1029/2012gl051441
|View full text |Cite
|
Sign up to set email alerts
|

Argo profiles variability of barrier layer in the tropical Indian Ocean and its relationship with the Indian Ocean Dipole

et al.

Abstract: [1] Interannual variability of the barrier layer (BL) in the southeastern tropical Indian Ocean (SETIO) is examined using temperature and salinity profiles derived from Argo floats since 2004. We show that a quasi-permanent BL exists off Sumatra with a semi-annual cycle and a maximum in November. Further, interannual variability of the BL is closely related to the Indian Ocean Dipole (IOD) with the IOD leading the BL by one month. During the 2006 positive IOD (pIOD) season, equatorial easterly-induced upwellin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
72
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(84 citation statements)
references
References 31 publications
11
72
1
Order By: Relevance
“…(GeoB 10013-1 and 10018-1). This pattern supports previous findings that the low-salinity tongue off western Sumatra (and thus,  18 O SW ), particularly in the fore-arc basins of Mentawai, Nias and Simeulue, ''is linked to the freshwater input in the near-surface layer from rainfall and river runoff'' 43 rather than ocean advection. Sprintall et al 44 and Janowiak and Xie 45 also stated that the freshwater pool located on the equator off the west Sumatra coast is related to a regional maximum in precipitation, as well as contribution from river runoff.…”
Section: Modern Climate Of the Study Areasupporting
confidence: 90%
“…(GeoB 10013-1 and 10018-1). This pattern supports previous findings that the low-salinity tongue off western Sumatra (and thus,  18 O SW ), particularly in the fore-arc basins of Mentawai, Nias and Simeulue, ''is linked to the freshwater input in the near-surface layer from rainfall and river runoff'' 43 rather than ocean advection. Sprintall et al 44 and Janowiak and Xie 45 also stated that the freshwater pool located on the equator off the west Sumatra coast is related to a regional maximum in precipitation, as well as contribution from river runoff.…”
Section: Modern Climate Of the Study Areasupporting
confidence: 90%
“…The region we studied is characterized by intense convective precipitation, where a fresher water cap and salinity stratified barrier layer commonly exist (e.g., Masson et al 2004;Qu and Meyers 2005). A few studies revealed that the barrier layer is important to the heat exchange between the mixed layer and thermocline, thus having impact on the evolution of the IOD (e.g., Du et al 2005;Du and Xie 2008;Qiu et al 2012), like its role in the ENSO dynamics (e.g., Delcroix and McPhaden 2002;Qu et al 2014). This work suggests there was a feedback between low-salinity water, thin mixed layer, and SST increase.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…6b,c). Recent studies suggested that the 2010 event might be the most significant negative IOD event in the recent decade (e.g., Qiu et al 2012). Two weak positive IOD events occurred successively in 2011 and 2012, reflected in SSS.…”
Section: A Sss Variation In the Equatorial Regionmentioning
confidence: 99%
See 1 more Smart Citation
“…The BL forms a barrier to the entrainment and turbulent mixing of cold thermocline water into the mixed layer and inhibits the momentum of downward mixing Delecluse 1998a, 1998b). The formation mechanisms and seasonal variations of the BLs differ from region to region (Sato et al 2004(Sato et al , 2006, and they are deeply involved in the Indian Ocean Dipole (IOD; Saji et al 1999) (Masson et al 2004;Qiu et al 2012) and ENSO (Ando and McPhaden 1997;Maes et al 2002Maes et al , 2005Maes et al 2006). Previous studies have noted that the BL shows various responses to atmospheric forcing associated with westerly wind bursts and the continuous precipitation of the Madden-Julian oscillation (MJO; Madden and Julian 1971) (Cronin and McPhaden 2002;DeMott et al 2015;Drushka et al 2014).…”
Section: Introductionmentioning
confidence: 99%